2020
DOI: 10.1002/hep4.1571
|View full text |Cite
|
Sign up to set email alerts
|

LPCN 1144 Resolves NAFLD in Hypogonadal Males

Abstract: Hypogonadism affects hepatic lipid metabolism and is expected to promote nonalcoholic fatty liver disease (NAFLD). The aims of this study were to determine (1) the prevalence of NAFLD in hypogonadal males and (2) the impact of correction of hypogonadism by LPCN 1144 (Lipocine, Inc., Salt Lake City, UT), an oral testosterone prodrug, on NAFLD in this population. Data were derived from a multicenter open-label single-arm trial of LPCN 1144 for hypogonadal males, in which a subset (n = 36) had serial magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The improvement of liver injury markers (alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, and gamma‐glutamyl transferase) in the majority of subjects was consistent with the results from a clinical study also utilizing the same dosing regimen of oral TU with no titration for four months that measured hepatic fat content. 19 As an analysis result of secondary efficacy endpoints evaluating T Cmax outliers, two of the three secondary endpoints (1.8 × ULN ≤ T Cmax ≤ 2.5 × ULN in ≤5% of subjects, and T Cmax > 2.5 × ULN in zero subjects) were met (5% and 0%, respectively) while the third secondary endpoint was not met but nearly achieved (82% with T Cmax ≤ 1.5 × ULN, target ≥85%). The results of secondary endpoints were comparable with a recently approved oral TU product with titration (83% with T Cmax ≤ 1.5 × ULN, 3% with 1.8 × ULN ≤ T Cmax ≤ 2.5 × ULN, and 3% with T Cmax > 2.5 × ULN).…”
Section: Discussionmentioning
confidence: 96%
“…The improvement of liver injury markers (alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, and gamma‐glutamyl transferase) in the majority of subjects was consistent with the results from a clinical study also utilizing the same dosing regimen of oral TU with no titration for four months that measured hepatic fat content. 19 As an analysis result of secondary efficacy endpoints evaluating T Cmax outliers, two of the three secondary endpoints (1.8 × ULN ≤ T Cmax ≤ 2.5 × ULN in ≤5% of subjects, and T Cmax > 2.5 × ULN in zero subjects) were met (5% and 0%, respectively) while the third secondary endpoint was not met but nearly achieved (82% with T Cmax ≤ 1.5 × ULN, target ≥85%). The results of secondary endpoints were comparable with a recently approved oral TU product with titration (83% with T Cmax ≤ 1.5 × ULN, 3% with 1.8 × ULN ≤ T Cmax ≤ 2.5 × ULN, and 3% with T Cmax > 2.5 × ULN).…”
Section: Discussionmentioning
confidence: 96%
“…Our results are consistent with a recent study in which 32 men with low serum testosterone, of whom 8 (25%) had type 2 diabetes, were given a novel oral testosterone preparation LPCN 1144 for 16 wk. In this study, 21/32 patients met diagnostic criteria for NAFLD, and a mean relative reduction in liver fat of 33% as measured by MRI-PDFF was demonstrated in 17 of these 21 patients[ 16 ]. However, in contrast to our study, the LPCN 1144 study did not include a control group.…”
Section: Discussionmentioning
confidence: 99%
“…A placebo controlled study of obese men with severe obstructive sleep apnoea and testosterone concentrations that ranged from low normal to normal demonstrated that testosterone therapy reduced liver fat as measured by computed tomography[ 15 ]. A study of 21 men with low serum testosterone concentrations and NAFLD reported that treatment with a novel oral testosterone prodrug improved liver fat as measured by magnetic resonance imaging proton density fat fraction (MRI-PDFF) in 81% of patients[ 16 ]. Two small studies of testosterone therapy in men with type 2 diabetes and low testosterone concentrations and one in men with mobility limitation and low testosterone concentrations conversely showed no significant change in hepatic fat compared to placebo as measured by MRI[ 17 - 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, the general improvement in liver histological and mRNA expression of markers related to the inflammation, steatosis and fibrosis was substantiated by the significant reduction of liver triglycerides content. In a recently performed 16-week clinical trial with LPCN 1144 in hypogonadal patients with NAFLD, LPCN 1144 reduced liver fat contents (measured by Magnetic Resonance Imaging Proton Density Fat Fraction, MRI-PDFF) by about 40% from baseline and resolved NAFLD in about half of the population [ 51 ]. The observation of the reduction of liver triglyceride content in this pre-clinical study supports the findings in the clinical study.…”
Section: Discussionmentioning
confidence: 99%